Enhancing Lempangang Village Youth Skills in Electronic Equipment Repair for Technological Independence - Akil, Muhammad; Syafar , Faisal; Sabara, Edy; Najamuddin, Faisal (Journal of Community Services and Engagement: Voice of Community (VOC), 2025)
The household electronic appliance maintenance and repair training for the Lempangang Village Youth Organization (Karang Taruna) aims to improve the technical skills of the community, particularly young people, in identifying and repairing damage to household electronic appliances. Through this training, participants gained knowledge and practical skills in using measuring tools such as multimeters, replacing damaged components, and performing preventative maintenance on irons. The training results showed a significant improvement in participants' skills, as evidenced by a 9.04% increase in pre- and post-test scores. In the pre-test, participants' average scores were around 60%-70%, indicating sufficient basic understanding, but with some areas for improvement. After the training, participants' post-test scores increased to 80%-90%, reflecting a clear improvement in their ability to independently repair electric irons. Furthermore, this training opened new business opportunities in the field of electronic appliance repair services, had a positive impact on local economic empowerment, and reduced electronic waste by extending the lifespan of existing appliances. The program also raised awareness about the importance of maintaining electronic appliances in the household. As a suggestion, expanding training materials and using digital technology to support further learning can increase the impact of this training, as well as expanding community participation through partnerships with various parties.